Probabilistic Tsunami Hazard Assessment in Meso and Macro Tidal Areas. Application to the Cádiz Bay, Spain - González, Mauricio; Álvarez-Gómez, José A.; Aniel-Quiroga, Íñigo; Otero, Luis; Olabarrieta, Maitane; Omira, Rachid; Luceño, Alberto; Jelinek, Robert; Krausmann, Elisabeth; Birkman, Joern; Baptista, Maria A.; Miranda, Miguel; et al. (Frontiers in Earth Science, 2021)
Tsunami hazard can be analyzed from both deterministic and probabilistic points of view. The deterministic approach is based on a “credible” worst case tsunami, which is often selected from historical events in the region of study. Within the probabilistic approach (PTHA, Probabilistic Tsunami Hazard Analysis), statistical analysis can be carried out in particular regions where historical records of tsunami heights and runup are available. In areas where these historical records are scarce, synthetic series of events are usually generated using Monte Carlo approaches. Commonly, the sea level variation and the currents forced by the tidal motion are either disregarded or considered and treated as aleatory uncertainties in the numerical models. However, in zones with a macro and meso tidal regime, the effect of the tides on the probability distribution of tsunami hazard can be highly important. In this work, we present a PTHA methodology based on the generation of synthetic seismic catalogs and the incorporation of the sea level variation into a Monte Carlo simulation. We applied this methodology to the Bay of Cádiz area in Spain, a zone that was greatly damaged by the 1755 earthquake and tsunami. We build a database of tsunami numerical simulations for different variables: faults, earthquake magnitudes, epicenter locations and sea levels. From this database we generate a set of scenarios from the synthetic seismic catalogs and tidal conditions based on the probabilistic distribution of the involved variables. These scenarios cover the entire range of possible tsunami events in the synthetic catalog (earthquakes and sea levels). Each tsunami scenario is propagated using the tsunami numerical model C3, from the source region to the target coast (Cádiz Bay). Finally, we map the maximum values for a given probability of the selected variables (tsunami intensity measures) producing a set of thematic hazard maps. 1000 different time series of combined tsunamigenic earthquakes and tidal levels were synthetically generated using the Monte Carlo technique. Each time series had a 10000-year duration. The tsunami characteristics were statistically analyzed to derive different thematic maps for the return periods of 500, 1000, 5000, and 10000 years, including the maximum wave elevation, the maximum current speed, the maximum Froude number, and the maximum total forces.